A Protracted Course of Periorbital Oedema in Infectious Mononucleosis Caused by Epstein-Barr Virus - Daryl Ricardo (MDPI AG, 2022)
Infectious mononucleosis (IM) is a viral disease most commonly caused by the Epstein-Barr virus (EBV). The triad of fever, pharyngitis, and cervical chain lymphadenopathy classically describe this benign condition. Ocular association is also possible, although less commonly reported, and manifests as bilateral periorbital oedema presenting early in the disease process. A case of a fit and well 18-year-old female patient who developed periorbital oedema before the classic triad is presented. Furthermore, her case describes a significantly longer duration of periorbital tissue involvement, contrary to what is described in the current literature. Clinicians should not only recognise periorbital oedema as an initial manifestation of IM but also be alerted of its possible protracted course.